Atributos químicos e físicos do solo após reaplicação de lodos de esgoto, escória de aciaria e lama cal em sistema semeadura direta - Miggiolaro, Alessandra Elena [UNESP] (2014)
The practical use of urban and industrial wastes in agriculture has been one of the promising alternatives to dispose of them without harming the environment, in addition to providing improvements in propriendades chemical, physical and biological soil properties, this study aimed to evaluate the changes chemical, physical and biological soil occurred in the absorption of nutrients and potentially toxic heavy metals, and its effects on the development of soybean, oats and sorghum grown under direct seeding system in the harvest of 2009/2010 and 2010/2011 . The work was developed in the field at the Experimental Farm Lageado - FCA / UNESP, Botucatu-SP in a distrophic Rhodic Haplustox, under tropical highland climate Cwa . The experimental design was randomized blocks in a 4x4 factorial with four replications . The treatments consisted of four residues, two sewage sludge, one centrifuged with virgin line ( LC ) and a biodigester ( LB ) and two industrial wastes, the slag ( E) and aquous line ( LCAL ) reapplied at dosages of 0, 2, 4 and 8 Mg ha- 1. Reapplication of waste LB, LC, LCAL and E in doses 2 to 8 Mg ha - 1 in direct sowing system provided improvements in chemical, physical and biological soil . The residue LB increasing content of Zn in the dosage 8 Mg ha- 1 as well as the zinc content in the soybean leaf, oat and sorghum. Reapplication of waste LB, LC, LCAL and E at doses up to 8 Mg ha - 1, three and fifteen months after reapplication not provide soil contamination by potentially toxic heavy metals studied depths . The resudue LC, LCAL and E may be used as soil acidity correctors, since neutralizes the acidity of the soil and provides the ground Ca and Mg, and provide P, K, S, and micronutrientes the ground.